Attention to diversity from mentoring (Journal of Parents and Teachers, 2023)
Attending to diversity in tutoring is a task that involves vocation, commitment, training and always having an attitude of continuous learning. Teamwork is essential to be able to detect, diagnose and carry out all the changes within the classroom that help each student, from their diversity and needs, to learn and develop to the maximum, without their own personal, family or social barriers being a brake on their maturation and learning process.
Keywords: empathy; integration; equipment; training; active methodologies